A Study of Personal Email Messages (Journal of the College of Basic Education, 2022)
This paper attempts to study some of the linguistic features of email messages or electronic mail messages as a means of communication and to find out whether emails; i.e. email messages can be considered as having features of the spoken language only or the written language only or both, or to regard emails as having a completely different language of communication, a language of its own that has its unique characteristics which do not exist neither in speech nor in writing. The corpus of analysis is 10 personal messages sent to the author